Aqueous lithium iron phosphate and preparation method thereof

By adding a second carbon cladding layer on the surface of lithium iron phosphate and using an organic polymer containing hydrophilic groups, the problem of difficult dispersion of the cathode material of lithium ion battery in water is solved, and efficient dispersion and excellent electrical properties are achieved. At the same time, it avoids contamination and high costs of organic solvents.

CN119419262AActive Publication Date: 2025-02-11SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411476963.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-11
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials are difficult to disperse in water, resulting in a degradation of electrical properties, and the use of organic solvents such as NMP will cause environmental pollution and high costs.

Method used

By adding a second carbon coating layer on the surface of lithium iron phosphate, using hydrophilic groups-containing organic polymers as the coating material, the hydrophobic properties of the material are changed so that it can achieve the previous dispersion in the oily solvent in water Effect.

Benefits of technology

It realizes efficient dispersion of lithium iron phosphate materials in aqueous solvents, avoids environmental pollution and high costs of using organic solvents, and improves the electrical properties of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419262A_ABST
    Figure CN119419262A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery positive electrode materials, in particular to aqueous lithium iron phosphate and a preparation method thereof. The aqueous lithium iron phosphate comprises a lithium iron phosphate inner core, a first carbon coating layer wrapping the inner core, and a second carbon coating layer wrapping the first carbon coating layer, wherein the raw material of the second carbon coating layer comprises an organic polymer containing a hydrophilic group; wherein the percentage of the mass of the second carbon coating layer to the mass of the aqueous lithium iron phosphate is W, and the particle sizes D10, D50 and D90 of the aqueous lithium iron phosphate meet the inequality: 0.05 < = W * (D90-D10) / D50 * 100 < = 10.00, and 0.05% < = W < = 1.0%. The aqueous lithium iron phosphate is stable in structure and can be dispersed by using water as a solvent, so that high cost and environmental pollution caused by using an organic solvent are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to aqueous lithium iron phosphate and a preparation method thereof. Background Art

[0002] At present, the positive electrode slurry of lithium-ion batteries generally uses fluorinated polymers such as polyvinylidene fluoride as a binder and organic solvents such as NMP (N-methylpyrrolidone) as a solvent. However, organic solvents are easy to cause environmental pollution and harm the health of operators, so it is necessary to add equipment and operating procedures to recycle organic solvents in production. However, the recycling process cannot achieve the full recovery of organic solvents. Even if secondary recycling is carried out, there will be incomplete recycling and environmental pollution after volatilization; and recycling it will consume a lot of energy, increasing the cost of the coating and drying process; at the same time, NMP itself as an industrial solvent needs to be purchased separately, which also increases the cost.

[0003] The lithium iron phosphate cathode material currently used in industry has extremely high hydrophobicity due to its nano-sized particles and the surface is coated with single carbon. It aggregates in water and cannot be evenly dispersed, which will lead to a decrease in the electrical properties of the material. This has led to the inability of low-cost, less polluted water to be used as a solvent for lithium iron phosphate cathode materials. If the aqueous lithium iron phosphate existing in the prior art is to be dispersed in water, a large amount of surfactants, thickeners, etc. need to be added during the preparation process, and specific high-temperature stirring and other steps are also required to increase the dispersion effect of the lithium iron phosphate material. The preparation process is too cumbersome and does not fundamentally change the hydrophobic and difficult-to-disperse material properties of lithium iron phosphate. Summary of the invention

[0004] Therefore, the purpose of the present invention is to provide an aqueous lithium iron phosphate and a preparation method thereof, the purpose of which is to increase hydrophilic functional groups on the surface of the lithium iron phosphate through a second layer coating, fundamentally changing the hydrophobic properties of the material, so that the material can achieve the dispersion effect in the previous oily solvent in the aqueous solvent without adding additional substances and steps to improve the dispersibility. When the aqueous lithium iron phosphate is used as a positive electrode material, water can be used as a solvent to disperse it for subsequent coating, avoiding the high cost and environmental pollution caused by the use of organic solvents.

[0005] To this end, the present invention provides the following technical solutions.

[0006] The aqueous lithium iron phosphate provided by the present invention comprises a lithium iron phosphate core, a first carbon coating layer wrapped outside the core, and a second carbon coating layer wrapped outside the first carbon coating layer, wherein the raw material of the second carbon coating layer comprises an organic polymer containing a hydrophilic group; wherein the mass of the second carbon coating layer accounts for a percentage of the mass of the aqueous lithium iron phosphate as W, and the particle sizes D10, D50, and D90 of the aqueous lithium iron phosphate satisfy the inequality: 0.05≤W×(D90-D10) / D50×100≤10.00, 0.05%≤W≤1.0%. The above-mentioned hydrophilic groups include, but are not limited to, one or more of hydroxyl groups, ether bonds, carboxyl groups, ester groups, and phosphate groups.

[0007] Optionally, the particle size of the aqueous lithium iron phosphate is: D10 is 0.1-1.0 μm, D50 is 0.2-2.0 μm, and D90 is 1.0-10.0 μm.

[0008] Optionally, the mass of the first carbon coating layer is 0.5% to 2% of the mass of the aqueous lithium iron phosphate. Typically, but not limitedly, the test method can be to use a carbon-sulfur tester to test the carbon content of the sample coated with the first carbon coating layer to obtain the mass of the first carbon coating layer; further, the carbon-sulfur tester can also be used to test the carbon content of the sample coated with the second carbon coating layer, and the mass of the second carbon coating layer is obtained by deducting the mass of the first carbon coating layer from the obtained result; finally, the ratio of the mass of the first carbon coating layer to the mass of the aqueous lithium iron phosphate and the ratio of the mass of the second carbon coating layer to the mass of the aqueous lithium iron phosphate are calculated.

[0009] Optionally, the thickness of the second carbon coating layer is 1-10 nm; typically but not limitedly, it can be measured by TEM.

[0010] Optionally, the organic polymer containing a hydrophilic group includes one or more of polyvinyl alcohol, polyacrylic acid, polyacrylate, and polyvinyl ether. Among them, polyacrylate includes polymethyl acrylate, polyethyl acrylate, etc., and polyvinyl ether includes polyvinyl methyl ether, polyvinyl ethyl ether, etc.

[0011] The present invention provides a method for preparing the aqueous lithium iron phosphate, comprising the following steps: S1: mixing a lithium source, an iron source, a phosphorus source, and a carbon source in a liquid medium to obtain a slurry, grinding, spray drying, sintering under a protective atmosphere, and crushing to obtain lithium iron phosphate particles having a first carbon coating layer; S2: mixing the lithium iron phosphate particles having the first carbon coating layer and the organic polymer containing a hydrophilic group, spray drying, sintering under a protective atmosphere, and crushing to obtain the aqueous lithium iron phosphate.

[0012] In the preparation method of aqueous lithium iron phosphate, typically and non-limitingly, the control of the quality of the second carbon coating layer can be carried out in advance by performing a thermogravimetric analysis of the organic polymer containing a hydrophilic group at the corresponding temperature and atmosphere to determine the mass percentage of the residue after sintering, and use this as the mass percentage of the second carbon coating layer that can be generated, and the amount of the organic polymer containing a hydrophilic group used can be reversed according to the planned coating amount. The thickness of the second carbon coating layer can be controlled according to the planned coating amount.

[0013] In the preparation method of aqueous lithium iron phosphate, typically but not limitedly, spray drying uses a centrifugal sprayer, the temperature in the spray tower is controlled to be 240°C ± 20°C, the hot air temperature at the air inlet is 280±20°C, the hot air temperature at the air outlet is 200±20°C, the tolerance is the maximum acceptable equipment accuracy, and the equipment setting parameters are center values.

[0014] Optionally, in S1, the sintering temperature is 740-800° C. and the sintering time is 6-12 hours.

[0015] Optionally, in S1, the molar ratio of lithium element, iron element and phosphorus element in the lithium source, iron source and phosphorus source is 1.00-1.10:1.00:1.00-1.10.

[0016] Optionally, in S1, the mass of the carbon source is 1% to 10% of the mass of the theoretical lithium iron phosphate; wherein the mass of the theoretical lithium iron phosphate is calculated based on the amount of iron element used, and the molar ratio of the iron element to the theoretical lithium iron phosphate is 1:1.

[0017] Optionally, in S1, the mass of the liquid medium is 5 to 10 times the sum of the masses of the lithium source, the iron source, the phosphorus source and the carbon source.

[0018] Optionally, the particle size D10 of the lithium iron phosphate particles having the first carbon coating layer is 0.1-1.0 μm, D50 is 0.2-2.0 μm, and D90 is 1.0-10.0 μm.

[0019] Optionally, in S1, the method of mixing the lithium source, iron source, phosphorus source and carbon source in the liquid medium comprises mixing them using a stirrer; optionally, the mixing time is 0.5 to 1 hour.

[0020] Optionally, in S1, the grinding is to grind the D50 of the particles in the slurry to 0.2-1.5 μm.

[0021] Optionally, in S1, the equipment used for grinding includes a sand mill.

[0022] Optionally, in S2, the sintering temperature is 400-480° C. and the sintering time is 3-8 hours.

[0023] Optionally, in S2, the organic polymer containing a hydrophilic group is prepared into a solution before mixing; optionally, in the organic polymer solution containing a hydrophilic group, the solvent includes one or more of water, methanol, ethanol, and acetone. Since the function of the solution is to ensure that the organic polymer is evenly dispersed on the surface of the material after the solvent is completely evaporated by spray drying, it is only necessary to ensure that the organic polymer is completely dissolved in the solution, and the concentration of the solution will not have an impact.

[0024] Optionally, the lithium source includes one or more of lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium nitrate, lithium carbonate, lithium phosphate, and lithium hydroxide.

[0025] Optionally, the iron source includes one or more of ferric phosphate, iron oxide, ferrous oxalate, iron, and ferric nitrate.

[0026] Optionally, the phosphorus source includes one or more of iron phosphate, diammonium phosphate, ammonium phosphate, lithium phosphate, and phosphoric acid.

[0027] Optionally, the carbon source includes one or more of citric acid, glucose, sucrose, and polyethylene glycol.

[0028] Optionally, the liquid medium includes one or more of water, methanol, ethanol, and acetone.

[0029] Optionally, the protective atmosphere includes at least one of nitrogen, inert gas, and carbon dioxide.

[0030] Optionally, the pulverizing method includes jet pulverization.

[0031] The present invention also provides a positive electrode plate, comprising the aqueous lithium iron phosphate or the aqueous lithium iron phosphate prepared by the above preparation method.

[0032] The present invention also provides a lithium-ion battery, comprising the above-mentioned positive electrode plate, and also comprising a negative electrode plate, a separator and an electrolyte.

[0033] In summary, the beneficial effects achieved by the present invention are:

[0034] The aqueous lithium iron phosphate provided by the present invention comprises a lithium iron phosphate core, a first carbon coating layer wrapped outside the core, and a second carbon coating layer wrapped outside the first carbon coating layer, wherein the raw material of the second carbon coating layer comprises an organic polymer containing a hydrophilic group; wherein the percentage of the mass of the second carbon coating layer to the mass of the aqueous lithium iron phosphate is W, and the particle sizes D10, D50, and D90 of the aqueous lithium iron phosphate satisfy the inequality: 0.05≤W×(D90-D10) / D50×100≤10.00, 0.05%≤W≤1.0%. The aqueous lithium iron phosphate has a stable structure, and the raw material of the second carbon coating layer includes an organic polymer containing a hydrophilic group. At the same time, the percentage of the mass of the second carbon coating layer to the mass of the aqueous lithium iron phosphate is controlled within the range of 0.05≤W×(D90-D10) / D50×100≤10.00, 0.05%≤W≤1.0%, so that when the aqueous lithium iron phosphate is used as a positive electrode material, water can be used as a solvent to disperse it for subsequent coating. And the aqueous lithium iron phosphate provided in the present invention, when using water as a solvent for dispersion, the solid content of the slurry can reach more than 55%, the upper limit of the coating surface density can reach more than 18.5mg / cm2, and the viscosity increase after standing for 6 hours is small, which is convenient for its processing and use. At the same time, the positive electrode sheet prepared by using the aqueous lithium iron phosphate provided in the present invention and dispersing it with water as a solvent can reach 157.7 mAh / g or more at 0.1C material gram capacity and 146.4 mAh / g or more at 1C material gram capacity after assembling into a battery, and the 200-cycle capacity retention rate at 1C can reach 97.9% or more, with excellent electrical performance. The aqueous lithium iron phosphate provided in the present invention can avoid the high cost and environmental pollution caused by the use of organic solvents in the battery preparation process.

[0035] The preparation method of aqueous lithium iron phosphate provided by the present invention comprises the following steps: S1: mixing a lithium source, an iron source, a phosphorus source, and a carbon source in a liquid medium to obtain a slurry, grinding, spray drying, sintering under a protective atmosphere, and crushing to obtain lithium iron phosphate particles having a first carbon coating layer; S2: mixing the lithium iron phosphate particles having the first carbon coating layer and the organic polymer containing a hydrophilic group, spray drying, sintering under a protective atmosphere, and crushing to obtain the aqueous lithium iron phosphate. The preparation method is simple, does not require a harsh preparation environment, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 It is a schematic diagram of the process of the preparation method of the present invention. DETAILED DESCRIPTION

[0038] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0040] Example 1

[0041] This embodiment provides an aqueous lithium iron phosphate and a preparation method thereof. The flow chart of the preparation method is as follows: Figure 1 As shown, the specific steps include:

[0042] (1) Weigh 2.45 g of lithium hydroxide, 15.00 g of solid iron phosphate, and 1.0 g of glucose, pour them into 150 g of deionized water in turn, stir them on an automatic stirrer for 1 h to mix evenly, pour them into a sand mill and grind them for 1 h. The particle size D50 of the slurry obtained is tested to be 0.4 μm, spray dried (using a centrifugal sprayer, the temperature in the spray tower is controlled to be 240°C ± 20°C, the hot air temperature at the air inlet is 280 ± 20°C, the hot air temperature at the air outlet is 200 ± 20°C, the tolerance is the maximum acceptable equipment accuracy, and the equipment setting parameters are the center value), and then transfer to a nitrogen atmosphere and sinter at 760°C for 8 h. After cooling, air flow crushing is performed, and the crushed particle size D10 is 0.2 μm, D50 is 0.5 μm, and D90 is 2.0 μm, thereby obtaining lithium iron phosphate particles (LFP-1) with a first carbon coating layer.

[0043] (2) Weigh 10.00 g of LFP-1 prepared in (1) and 100 g of polyvinyl alcohol solution (the solvent is water and the solute polyvinyl alcohol is 0.1 g), mix them evenly, and spray dry (using a centrifugal sprayer, the temperature in the spray tower is controlled to 240°C ± 20°C, the hot air temperature at the air inlet is 280±20°C, the hot air temperature at the air outlet is 200±20°C, the tolerance is the maximum acceptable equipment accuracy, and the equipment setting parameter is the center value), then sinter at 460°C for 5 h in a nitrogen atmosphere, cool, and perform air flow crushing. The crushed particle size D10 is 0.2 μm, D50 is 0.5 μm, and D90 is 2.0 μm, thereby obtaining aqueous lithium iron phosphate (LFP-A).

[0044] Part of LFP-1 was tested for carbon content using a carbon-sulfur tester to obtain the mass of the first carbon coating layer; part of LFP-A was tested for carbon content using a carbon-sulfur tester, and the mass of the second carbon coating layer was obtained by deducting the mass of the first carbon coating layer from the obtained result. The mass of the first carbon coating layer was calculated to be 1.33% of the mass of the water-based LFP-A, and the percentage W of the mass of the second carbon coating layer to the mass of the water-based LFP-A was 0.62%, W×(D90-D10) / D50×100=2.23. The thickness of the second carbon coating layer was measured by transmission electron microscopy TEM to be 7nm.

[0045] Example 2

[0046] This embodiment provides an aqueous lithium iron phosphate and a preparation method thereof. The flow chart of the preparation method is as follows: Figure 1 As shown, the specific steps include:

[0047] (1) Weigh 3.87 g of lithium carbonate, 15.00 g of solid iron phosphate, and 1.2 g of solid ammonium sucrose, and pour them into 180 g of 50% ethanol solution in turn, stir on an automatic stirrer for 0.5 h to mix evenly, pour into a sand mill and grind for 0.6 h, test the particle size D50 of the slurry obtained to be 0.6 μm, spray dry (using a centrifugal sprayer, the temperature in the spray tower is controlled to 240°C ± 20°C, the hot air temperature at the air inlet is 280 ± 20°C, the hot air temperature at the air outlet is 200 ± 20°C, the tolerance is the maximum acceptable equipment accuracy, and the equipment setting parameters are the center value), then transfer to an argon atmosphere and sinter at 780°C for 6 h. After cooling, perform air flow crushing, the crushed particle size D10 is 0.3 μm, D50 is 0.8 μm, and D90 is 5 μm, to obtain lithium iron phosphate particles (LFP-2) with a first carbon coating layer.

[0048] (2) Weigh 10.00 g of LFP-2 prepared in (1) and 80 g of polyvinyl methyl ether solution (the solvent is methanol and the solute polyvinyl methyl ether is 0.08 g), mix them evenly, spray dry (using a centrifugal sprayer, the temperature in the spray tower is controlled to 240°C ± 20°C, the hot air temperature at the air inlet is 280±20°C, the hot air temperature at the air outlet is 200±20°C, the tolerance is the maximum acceptable equipment accuracy, and the equipment setting parameter is the center value), then sinter at 480°C for 3 h in an argon atmosphere, and after cooling, the coated material is air flow crushed, and the crushed particle size D10 is 0.3 μm, D50 is 0.8 μm, and D90 is 5 μm, to obtain aqueous lithium iron phosphate (LFP-B).

[0049] Among them, part of LFP-2 was tested for carbon content using a carbon-sulfur tester to obtain the mass of the first carbon coating layer; part of LFP-B was tested for carbon content using a carbon-sulfur tester, and the mass of the second carbon coating layer was obtained by deducting the mass of the first carbon coating layer from the obtained result, and the mass of the first carbon coating layer was calculated to be 1.60% of the mass of the water-based LFP-B, and the percentage W of the mass of the second carbon coating layer to the mass of the water-based LFP-B was 0.74%, W×(D90-D10) / D50×100=4.35. The thickness of the second carbon coating layer was measured by transmission electron microscopy TEM to be 8nm.

[0050] Example 3

[0051] This embodiment provides an aqueous lithium iron phosphate and a preparation method thereof. The flow chart of the preparation method is as follows: Figure 1 As shown, the specific steps include:

[0052] (1) Weigh 10.39 g of lithium dihydrogen phosphate, 14.30 g of ferrous oxalate solid, and 0.5 g of citric acid, and pour them into 170 g of 40% methanol solution in turn, stir on an automatic stirrer for 0.8 h to mix evenly, pour into a sand mill and grind for 0.5 h, test the particle size D50 of the slurry obtained to be 0.3 μm, spray dry (using a centrifugal sprayer, the temperature in the spray tower is controlled to 240°C ± 20°C, the hot air temperature at the air inlet is 280 ± 20°C, the hot air temperature at the air outlet is 200 ± 20°C, the tolerance is the maximum acceptable equipment accuracy, and the equipment setting parameter is the center value), then transfer to a nitrogen atmosphere and sinter at 780°C for 10 h, after cooling, perform air flow crushing, the crushed particle size D10 is 0.5 μm, D50 is 1.0 μm, and D90 is 2.0 μm, to obtain lithium iron phosphate particles (LFP-3) with a first carbon coating layer.

[0053] (2) Weigh 10.00 g of LFP-3 prepared in (1) and 120 g of polyacrylic acid solution (the solvent is ethanol and the solute polyacrylic acid is 0.02 g), mix them evenly, spray dry (using a centrifugal sprayer, the temperature in the spray tower is controlled to 240°C ± 20°C, the hot air temperature at the air inlet is 280±20°C, the hot air temperature at the air outlet is 200±20°C, the tolerance is the maximum acceptable equipment accuracy, and the equipment setting parameter is the center value), then sinter at 440°C for 6 h in an argon atmosphere, and after cooling, the coated material is air flow crushed, and the crushed particle size D10 is 0.5 μm, D50 is 1.0 μm, and D90 is 2.0 μm, to obtain aqueous lithium iron phosphate (LFP-C).

[0054] Among them, part of LFP-3 was tested for carbon content using a carbon-sulfur tester to obtain the mass of the first carbon coating layer; part of LFP-C was tested for carbon content using a carbon-sulfur tester, and the mass of the second carbon coating layer was obtained by deducting the mass of the first carbon coating layer from the obtained result. The mass of the first carbon coating layer was calculated to be 1.14% of the mass of the water-based LFP-C, and the percentage W of the mass of the second carbon coating layer to the mass of the water-based LFP-C was 0.12%, W×(D90-D10) / D50×100=0.18. The thickness of the second carbon coating layer was measured by transmission electron microscopy TEM to be 2nm.

[0055] Example 4

[0056] This embodiment provides an aqueous lithium iron phosphate and a preparation method thereof. The flow chart of the preparation method is as follows: Figure 1 As shown, the specific steps include:

[0057] (1) Weigh 2.45 g of lithium hydroxide, 15.00 g of solid iron phosphate, and 1.0 g of glucose, pour them into 150 g of deionized water in turn, stir them on an automatic stirrer for 1 h to mix evenly, pour them into a sand mill and grind them for 2 h. Test the particle size D50 of the slurry obtained to be 0.15 μm, spray dry (using a centrifugal sprayer, the temperature in the spray tower is controlled to 240°C ± 20°C, the hot air temperature at the air inlet is 280 ± 20°C, the hot air temperature at the air outlet is 200 ± 20°C, the tolerance is the maximum acceptable equipment accuracy, and the equipment setting parameters are the center value), then transfer to a nitrogen atmosphere and sinter at 740°C for 12 h. After cooling, perform air flow crushing, and the crushed particle size D10 is 0.1 μm, D50 is 0.2 μm, and D90 is 2.2 μm to obtain lithium iron phosphate particles (LFP-4) with a first carbon coating layer.

[0058] (2) Weigh 10.00 g of LFP-4 prepared in (1) and 100 g of polyvinyl alcohol solution (the solvent is water and the solute polyvinyl alcohol is 0.15 g), mix them evenly, spray dry (using a centrifugal sprayer, the temperature in the spray tower is controlled to 240°C ± 20°C, the hot air temperature at the air inlet is 280±20°C, the hot air temperature at the air outlet is 200±20°C, the tolerance is the maximum acceptable equipment accuracy, and the equipment setting parameters are the center value), then sinter at 400°C for 8 h in a nitrogen atmosphere, cool, and then perform air flow crushing. The crushed particle size D10 is 0.1 μm, D50 is 0.2 μm, and D90 is 2.2 μm, thereby obtaining aqueous lithium iron phosphate (LFP-D).

[0059] Among them, part of LFP-4 was tested for carbon content using a carbon-sulfur tester to obtain the mass of the first carbon coating layer; part of LFP-D was tested for carbon content using a carbon-sulfur tester, and the mass of the second carbon coating layer was obtained by deducting the mass of the first carbon coating layer from the obtained result, and the mass of the first carbon coating layer was calculated to be 1.29% of the mass of the water-based LFP-D, and the percentage W of the mass of the second carbon coating layer to the mass of the water-based LFP-D was 0.94%, W×(D90-D10) / D50×100=9.87. The thickness of the second carbon coating layer was measured by transmission electron microscopy TEM to be 10nm.

[0060] Example 5

[0061] This embodiment provides an aqueous lithium iron phosphate and a preparation method thereof. The flow chart of the preparation method is as follows: Figure 1 As shown, the specific steps include:

[0062] (1) Weigh 2.45 g of lithium hydroxide, 15.00 g of solid iron phosphate, and 1.0 g of glucose, pour them into 150 g of deionized water in turn, stir them on an automatic stirrer for 1 h to mix evenly, pour them into a sand mill and grind them for 0.3 h. Test the particle size D50 of the slurry obtained to be 1.5 μm, spray dry (using a centrifugal sprayer, the temperature in the spray tower is controlled to 240°C ± 20°C, the hot air temperature at the air inlet is 280 ± 20°C, the hot air temperature at the air outlet is 200 ± 20°C, the tolerance is the maximum acceptable equipment accuracy, and the equipment setting parameters are the center value), then transfer to a nitrogen atmosphere and sinter at 800°C for 6 h. After cooling, perform air flow crushing, and the crushed particle size D10 is 0.8 μm, D50 is 1.9 μm, and D90 is 3.1 μm, to obtain lithium iron phosphate particles (LFP-5) with a first carbon coating layer.

[0063] (2) Weigh 10.00 g of the LFP-5 prepared in (1) and 100 g of a polyvinyl alcohol solution (the solvent is water and the solute polyvinyl alcohol is 0.01 g), mix them evenly, and spray dry them (using a centrifugal sprayer, the temperature in the spray tower is controlled to be 240°C ± 20°C, the hot air temperature at the air inlet is 280±20°C, the hot air temperature at the air outlet is 200±20°C, the tolerance is the maximum acceptable equipment accuracy, and the equipment setting parameters are the center values), and then sinter them at 450°C for 6 h in a nitrogen atmosphere. After cooling, they are air flow crushed, and the crushed particle sizes D10, D50, and D90 are 0.8 μm, 0.9 μm, and 3.1 μm, to obtain aqueous lithium iron phosphate (LFP-E).

[0064] Among them, part of LFP-5 was tested for carbon content using a carbon-sulfur tester to obtain the mass of the first carbon coating layer; part of LFP-E was tested for carbon content using a carbon-sulfur tester, and the mass of the second carbon coating layer was obtained by deducting the mass of the first carbon coating layer from the obtained result. The mass of the first carbon coating layer was calculated to be 1.35% of the mass of the water-based LFP-E, and the percentage W of the mass of the second carbon coating layer to the mass of the water-based LFP-E was 0.06%, W×(D90-D10) / D50×100=0.07. The thickness of the second carbon coating layer was measured by transmission electron microscopy TEM to be 1 nm.

[0065] Comparative Examples 1 to 3

[0066] The lithium iron phosphate provided by Comparative Examples 1 to 3 are the lithium iron phosphate particles with the first carbon coating layer prepared in step (1) of Examples 1 to 3, respectively. Comparative Examples 1 to 3 correspond to Examples 1 to 3, respectively.

[0067] Comparative Example 4

[0068] This comparative example provides an aqueous lithium iron phosphate and a preparation method thereof, which is different from Example 2 only in that the mass of the solute polyethylene ether in the polyethylene ether solution used in step (2) is 0.24 g.

[0069] The mass of the first carbon coating layer is 1.6% of the mass of the aqueous LFP-F, the mass of the second carbon coating layer is 2.22% of the mass of the aqueous LFP-F, W×(D90-D10) / D50×100=13.05. The thickness of the second carbon coating layer is 21 nm as measured by transmission electron microscopy (TEM).

[0070] Comparative Example 5

[0071] This comparative example provides an aqueous lithium iron phosphate and a preparation method thereof, which is different from Example 3 only in that the mass of the solute polyacrylic acid in the polyacrylic acid solution used in step (2) is 0.005 g.

[0072] The mass of the first carbon coating layer was measured and calculated to be 1.14% of the mass of the aqueous LFP-G, the mass of the second carbon coating layer as a percentage of the mass of the aqueous LFP-G was 0.03%, W×(D90-D10) / D50×100=0.045. The thickness of the second carbon coating layer was measured by transmission electron microscopy (TEM) to be 0.5 nm.

[0073] Test Example 1 (Processing Performance)

[0074] The final products obtained in each embodiment and comparative example are mixed according to the mass ratio of LFP (lithium iron phosphate): CMC (carboxymethyl cellulose): SBR (styrene-butadiene rubber) = 96.5: 1.0: 2.5, and water is used as a solvent for homogenization. The amount of solvent water added is dynamically added according to the situation to ensure that the final discharge viscosity is within 5000-10000 cps (corresponding to the slurry viscosity value required for actual production of the enterprise). In specific operations, when the solid content of comparative examples 1, 2, and 3 is similar to that in the embodiment, the final product will be stuck in stirring and cannot be rotated due to poor dispersibility in water, so solvent water is continued to be added to reduce its solid content until it can be stirred smoothly, and then the solid content is recorded and subsequent operations such as viscosity testing are performed.

[0075] The initial viscosity and the viscosity after standing for 6 hours were tested, and the test results are shown in Table 1. The viscosity is directly measured by the viscosity tester, and the solid content is directly calculated by the addition amount of the material and the liquid component.

[0076] To test the upper limit of coating surface density, the specific operation is: first apply a thinner layer by scraping, and test its surface density after drying at 90°C. Then, increase the scraper spacing, apply again, and test its surface density after drying at 90°C. Repeat the above operation until cracks appear on the surface of the product after drying at 90°C. The surface density obtained by the previous operation before cracking is taken as the surface density of the corresponding product.

[0077] Table 1

[0078]

[0079] Test Example 2 (Electrode Moisture Residual and Electrical Performance)

[0080] The final products obtained in the examples and comparative examples were coated to a surface density of 14 mg / cm 2 The positive electrode sheet used is a nano 12um aluminum foil. Among them, sample examples 1 to 5, comparative examples 3-1, and comparative examples 4 to 5 use water as a solvent for dispersion, using the formula and method given in test example 1; sample comparative example 3-2 uses NMP as a solvent for dispersion, and the slurry solid content is controlled to be 62%. The coated positive electrode sheet is coated with 2.2mg / cm 3 The compaction density is compacted and rolled, and the positive electrode is vacuum-baked at 100℃ for 10h. After that, the residual moisture in the electrode is tested (Karl Fischer moisture tester at 170℃). A pair of lithium button batteries are assembled using a 2032 button battery shell (the negative electrode is a lithium sheet φ16mm×0.6mm, the electrolyte is Xinzhoubang A60, and the separator is uncoated Celgard2075).

[0081] The performance of the above lithium button battery was tested using the Blue Electric test system: 0.1C material gram capacity: at a room temperature of 25°C, charge to 3.75V at 0.1C, then discharge to 2.0V, repeat two cycles, and calculate its gram capacity with the second cycle data; 1C material gram capacity: at a room temperature of 25°C, charge to 3.75V at 1C, then discharge to 2.0V, calculate its gram capacity; 1C cycle 200 weeks capacity retention rate: at a room temperature of 25°C, charge to 3.75V at 1C, then discharge to 2.0V, cycle 200 weeks, and measure the material cycle capacity retention rate. The test results are shown in Table 2. Since Comparative Examples 1 and 2 are dispersed in water or NMP as the solvent, the data obtained are similar to Comparative Example 3, and are not given here.

[0082] Table 2

[0083]

[0084] As can be seen from Tables 1 and 2, when water is used as a dispersing solvent, the dispersibility (solid content) of the slurry of the final product prepared in the embodiment, the rebound (rise) amount of static viscosity after 6 hours, and the upper limit of the coating surface density are significantly better than those of Comparative Examples 1, 2, 3, and 5. This shows that the aqueous lithium iron phosphate material proposed in this application can be completely replaced by NMP for homogenous coating with water as a solvent, which reduces the production cost of the battery and reduces the harm of NMP to personnel and the environment. And the residual moisture content of the pole piece of the aqueous lithium iron phosphate positive electrode material prepared in Examples 1 to 3, the 0.1C and 1C capacity of the deducted electricity, and the 1C cycle retention rate are all equivalent to those of Comparative Example 3-2 using NMP as a dispersing solvent, indicating that the presence of the second carbon coating layer in the final product prepared in the embodiment and the use of water as a solvent for dispersion will not affect the electrical properties of the material. However, the residual moisture content and electrical properties of the pole piece of Comparative Example 3-1 using water as a dispersing solvent are far worse than those of the embodiment, which further proves that the product obtained in Comparative Example 3 cannot use water as a dispersing solvent. In the final product obtained in Comparative Example 4, the raw material of the second carbon coating layer includes an organic polymer containing a hydrophilic group, but W×(D90-D10) / D50×100 is greater than 10. Although the solid content and 6h static viscosity rebound (rise) data in Table 1 are good, it can be seen from Table 2 that after the battery is made, the residual moisture content of the pole piece and the subsequent electrical performance test are significantly deteriorated, and cannot be actually applied to production. For Comparative Example 5, in which the raw material of the second carbon coating layer includes an organic polymer containing a hydrophilic group, but W×(D90-D10) / D50×100 is less than 0.05, it can be seen that the dispersion (solid content) of the final product slurry, the rebound (rise) amount of the 6h static viscosity, and the coating surface density are all better than those of Comparative Examples 1, 2, and 3 without the second carbon coating layer; but the improvement in electrical performance is not large, far less than the improvement in the corresponding performance in the embodiment, and cannot meet the needs of actual production, and under water homogenization, the residual moisture content and electrical performance of the pole piece are seriously affected.

[0085] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the present invention.

Claims

1. An aqueous lithium iron phosphate, characterized in that: It comprises a lithium iron phosphate core, a first carbon coating layer wrapped outside the core, and a second carbon coating layer wrapped outside the first carbon coating layer, wherein the raw material of the second carbon coating layer comprises an organic polymer containing a hydrophilic group; The percentage of the mass of the second carbon coating layer to the mass of the aqueous lithium iron phosphate is W, and the particle sizes D10, D50, and D90 of the aqueous lithium iron phosphate satisfy the inequality: 0.05≤W×(D90-D10) / D50×100≤10.00, 0.05%≤W≤1.0%.

2. The aqueous lithium iron phosphate according to claim 1, characterized in that: The particle size of the aqueous lithium iron phosphate is: D10 is 0.1-1.0 μm, D50 is 0.2-2.0 μm, and D90 is 1.0-10.0 μm; And / or, the mass of the first carbon coating layer is 0.5% to 2% of the mass of the aqueous lithium iron phosphate; and / or, the thickness of the second carbon coating layer is 1 to 10 nm; And / or, the organic polymer containing a hydrophilic group includes one or more of polyvinyl alcohol, polyacrylic acid, polyacrylate, and polyvinyl ether.

3. A method for preparing aqueous lithium iron phosphate as claimed in claim 1 or 2, characterized in that: The steps include: S1: mixing a lithium source, an iron source, a phosphorus source, and a carbon source in a liquid medium to obtain a slurry, grinding, spray drying, sintering, and crushing under a protective atmosphere to obtain lithium iron phosphate particles having a first carbon coating layer; S2: mixing the lithium iron phosphate particles having the first carbon coating layer and the organic polymer containing the hydrophilic group, spray drying, sintering under a protective atmosphere, and crushing to obtain the aqueous lithium iron phosphate.

4. The preparation method according to claim 3, characterized in that: In S1, the sintering temperature is 740-800°C and the sintering time is 6-12h; And / or, in S1, the molar ratio of lithium element, iron element and phosphorus element in the lithium source, iron source and phosphorus source is 1.00-1.10:1.00:1.00-1.10; And / or, in S1, the mass of the carbon source is 1% to 10% of the theoretical mass of lithium iron phosphate; And / or, in S1, the mass of the liquid medium is 5 to 10 times the sum of the mass of the lithium source, the iron source, the phosphorus source, and the carbon source; And / or, the particle size D10 of the lithium iron phosphate particles having the first carbon coating layer is 0.1-1.0 μm, D50 is 0.2-2.0 μm, and D90 is 1.0-10.0 μm.

5. The preparation method according to claim 3 or 4, characterized in that: In S1, the method of mixing the lithium source, the iron source, the phosphorus source and the carbon source in the liquid medium comprises mixing them using a stirrer; optionally, the mixing time is 0.5 to 1 hour; And / or, in S1, grinding is grinding the D50 of the particles in the slurry to 0.2-1.5 μm; And / or, in S1, the equipment used for grinding includes a sand mill.

6. The preparation method according to any one of claims 3 to 5, characterized in that: In the step S2, the sintering temperature is 400-480°C and the sintering time is 3-8 hours.

7. The preparation method according to any one of claims 3 to 6, characterized in that: In S2, the organic polymer containing hydrophilic groups is prepared into a solution before mixing; optionally, in the organic polymer solution containing hydrophilic groups, the solvent includes one or more of water, methanol, ethanol, and acetone.

8. The preparation method according to any one of claims 3 to 7, characterized in that: The lithium source includes one or more of lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium nitrate, lithium carbonate, lithium phosphate, and lithium hydroxide; and / or, the iron source comprises one or more of ferric phosphate, ferric oxide, ferrous oxalate, iron, and ferric nitrate; And / or, the phosphorus source includes one or more of iron phosphate, diammonium phosphate, ammonium phosphate, lithium phosphate, and phosphoric acid; And / or, the carbon source includes one or more of citric acid, glucose, sucrose, and polyethylene glycol; And / or, the liquid medium includes one or more of water, methanol, ethanol, and acetone; And / or, the protective atmosphere includes at least one of nitrogen, inert gas, and carbon dioxide; And / or, the pulverizing method includes jet pulverization.

9. A positive electrode sheet, characterized in that: It includes the aqueous lithium iron phosphate as described in claim 1 or 2 or the aqueous lithium iron phosphate prepared by the preparation method as described in any one of claims 3 to 8.

10. A lithium ion battery, characterized in that: It includes the positive electrode sheet as described in claim 9, and also includes a negative electrode sheet, a separator and an electrolyte.

Citation Information

Patent Citations

  • Preparation method of three-layer carbon-coated composite lithium iron phosphate cathode material

    CN109920989A

  • Preparation method of lithium iron phosphate material

    CN111129492A

  • Lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery

    CN115332530A

  • Preparation method of water-based processing ferric sodium pyrophosphate

    CN116986569A

  • Lithium iron phosphate material, preparation method and application thereof and lithium ion battery

    CN118039883A